Internet browsing trends among Malaysians during movement control order (MCO) period - Isa, Khairunesa; Latiff, Azmi Abdul (EverScience Publications, 2020)
The Industrial Revolution Era 4.0 witnesses the indispensable role of Internet in consumers’ life. Many daily activities can be solved through the internet such as bill payment, ticket booking, accessibility to a variety of information and a host of other matters. The implementation of the Movement Control Order (MCO) as a result of the Covid-19 outbreak has led to the increase in internet traffic flows across the country by 23.5 per cent in the first week of MCO. The usage increased by 8.6 percent in the second week of the MCO. This study attempts to investigate the perception of Malaysian internet users on the level of internet accessibility, criteria that they consider in choosing websites to visit during MCO and differences in level of satisfaction with internet accessibility between male and female. A total number of 348 adults from 14 states in Malaysia provided valid responses to an online questionnaire. The findings show that the respondents’ perception on Internet accessibility is only at moderate level and there is no significant difference in the perception between male and female respondents. The findings also show that most of the respondents consider security and confidentiality, constant update of information and user-friendliness as the important criteria they use when browsing websites.